2019
DOI: 10.1021/acs.analchem.9b01248
|View full text |Cite
|
Sign up to set email alerts
|

Automated Nanoflow Two-Dimensional Reversed-Phase Liquid Chromatography System Enables In-Depth Proteome and Phosphoproteome Profiling of Nanoscale Samples

Abstract: Two-dimensional reversed-phase capillary liquid chromatography (2D RPLC) separations have enabled comprehensive proteome profiling of biological systems. However, milligram sample quantities of proteins are typically required due to significant losses during offline fractionation. Such a large sample requirement generally precludes the application samples in the nanogram to low-microgram range. To achieve in-depth proteomic analysis of such small-sized samples, we have developed the nanoFAC (nanoflow Fractiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 52 publications
1
64
0
Order By: Relevance
“…demonstrated to enable targeted quantification of the majority of epidermal growth factor receptor pathway proteins in 10-100 mammalian cells. We have also demonstrated that the addition of a MS-compatible detergent, n-Dodecyl -D-Maltoside (DDM), can significantly reduce surface adsorption for improving sample recovery 10 . Most importantly, we have recently developed a nanoPOTS (nanodroplet Processing in One Pot for Trace Samples) platform 11 to dramatically improve sample processing efficiency for small number of cells down to single cells.…”
Section: Downloaded Frommentioning
confidence: 99%
“…demonstrated to enable targeted quantification of the majority of epidermal growth factor receptor pathway proteins in 10-100 mammalian cells. We have also demonstrated that the addition of a MS-compatible detergent, n-Dodecyl -D-Maltoside (DDM), can significantly reduce surface adsorption for improving sample recovery 10 . Most importantly, we have recently developed a nanoPOTS (nanodroplet Processing in One Pot for Trace Samples) platform 11 to dramatically improve sample processing efficiency for small number of cells down to single cells.…”
Section: Downloaded Frommentioning
confidence: 99%
“…The sensitivity and depth of proteomic analysis have been improved through development of mass spectrometry (MS), pretreatment, and liquid chromatography (LC) separation technologies, which have made it possible to analyze lowly expressed proteins, including those of interest [2,3,4,5]. For deep proteomic analysis, multi-dimensional protein identification technology (MudPIT), in which digested peptides are fractionated on strong cation exchange, high-pH C18, and other LC columns followed by LC-MS/MS analysis, is the primary approach used [1,6,7,8,9]. Moreover, by combining MudPIT with isobaric tags, such as tandem mass tag and isobaric tags for relative and absolute quantification, in-depth comparative proteomic analysis is possible [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Reproducible and in-depth proteomic analysis of samples smaller than 500,000 cells requires signi cant improvements in sensitivity over standard approaches. The necessary technological improvements are actively being pursued in our lab (21,(33)(34)(35)(36) and others (20,(37)(38)(39) with great success in recent years. However, much more work is needed to make these technologies available to less specialized laboratories.…”
Section: Discussionmentioning
confidence: 99%